Emmer wheat eco-geographic and genomic congruence shapes phenotypic performance under mediterranean climate - Fadida-Myers, Aviya; Fuerst, Dana; Tzuberi, Aviv; Yadav, Shailesh; Nashef, Kamal; Roychowdhury, Rajib; Sansaloni, Carolina P.; Hübner, Sariel; Ben-David, Roi (MDPI, 2022)
Emmer wheat (Triticum turgidum ssp. dicoccum) is one of the world’s oldest domesticated crops, and it harbors a potentially rich reservoir of agronomic and nutritional quality trait variations. The growing global demand for plant-based health-food niche markets has promoted new commercial interest in ancient grains, including Emmer wheat. Although T. dicoccum can also perform well under harsh environments, its cultivation along the Mediterranean agro-ecosystems is sparse. Here, we analyze a unique tetraploid wheat collection (n = 121) representing a wide geographic range of Emmer accessions, using 9897 DArTseq markers and on-field phenotypic characterization to quantify the extent of diversity among populations and the interactions between eco-geographic, genetic, and phenotypic attributes. Population genomic inferences based on the DArTseq data indicated that the collection could be split into four distinguished clusters in accordance with their eco-geographic origin although significant phenotypic variation was observed within clusters. Superior early vegetative vigor, shorter plant height, and early phenology were observed among emmer wheat accessions from Ethiopia compared to accessions from northern regions. This adaptive advantage highlights the potential of emmer wheat as an exotic germplasm for wheat improvement through breeding. The direct integration of such germplasm into conventional or organic farming agro-systems under the Mediterranean basin climate is also discussed.